THE ROLE OF IDEALIZED INFLUENCE ON PERFORMANCE IN MARIST SECONDARY SCHOOLS IN NIGERIA (Cuea Journal of Business and Economics, 2025)
This research investigated the impact of idealized influence, a component of transformative leadership, on the performance of Marist secondary schools in Nigeria.  It emphasized how leaders' ethical behaviour, charisma, and embodiment of ideals foster trust and commitment among staff and pupils. The design of the survey was cross-sectional and descriptive.  One hundred and forty-one individuals, including educators and senior secondary school students, provided their responses.  There were three pupils chosen from seven different Marist schools.  Techniques of stratified random sampling and purposive sampling were used in this study.  The data were analysed using SPSS, which included Pearson correlation and multiple regression, and a standardized questionnaire was sent to the participants. Results revealed a strong positive correlation (r = 0.910) between idealized influence and school performance. Respondents confirmed that visionary and morally upright leadership significantly improves academic outcomes, teacher motivation, and institutional efficiency. The study enriches Bass’s transformational leadership theory by offering empirical support for the effectiveness of idealized influence. It recommends incorporating ethical leadership training into school leadership development and adopting idealized influence metrics in performance appraisals.